Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web di SMAN 1 Bengkalis - Mila, Mila; Nadila, Nadila; Kurniati, Suci; Rahmayani, Mentari Tri Indah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The information system in designing a web-based information system for new student admissions at SMAN 1 Bengkalis still uses a manual system.This design aims to develop the technology usedCurrently, such as designing the admissions information system at SMAN 1 Bengkalis. Admission of new students still often experiences problems such as data collection and the process of admission information which is still done manually through ledgers, so it takes a lot of time and energy to search for student data. In designing this information system, the SDLC method is used, the function of which is to develop and design high quality software. This information system uses a programming language.